(untitled) (Architecture Image Studies, 2025)
This study presents a comparative analysis of second-order effects in steel pipe rack structures based on two leading structural design codes: IS 800:2007 (Indian Standard) and AISC 360-16 (American Standard). The objective is to evaluate and contrast the influence of second-order effects—specifically P-Δ (global deformation) and P-δ (local deformation)—on the structural behavior, safety, and economy of a typical multi-tier steel pipe rack system. Using STAAD Pro CONNECT Edition, the pipe rack was modeled and analyzed under identical load conditions, including dead loads, live loads, wind loads (IS 875 and ASCE 7-16), thermal loads, and pipe operating conditions. The analysis incorporated geometric nonlinearity via the P-Delta method. IS 800:2007 employed traditional moment magnification techniques without stiffness reduction, while AISC 360-16 adopted the Direct Analysis Method (DAM) with τb factor adjustments and notional loads to capture initial imperfections. Results indicate that while both codes ensure structural safety, AISC 360-16 provides more conservative and optimized designs, particularly for slender members, by explicitly accounting for second-order effects. The study concludes that for complex industrial structures like pipe racks, AISC 360-16 offers greater reliability in terms of stability and material economy.